Sufentanil Disposition and Pharmacokinetic Model-Based Dosage Regimen for Sufentanil in Ventilated Full-Term Neonates - Pokorná, Pavla; Šíma, Martin; Koch, Birgit; Tibboel, Dick; Slanař, Ondřej (Pharmacology, 2021)
INTRODUCTION: Sufentanil is a potent synthetic opioid used for analgesia in neonates; however, data concerning drug disposition of sufentanil and dosage regimen are sparse in this population. Therefore, the aim of the study was to explore sufentanil disposition and to propose optimal loading and maintenance doses of sufentanil in ventilated full-term neonates. METHODS: Individual sufentanil pharmacokinetic parameters were calculated based on therapeutic drug monitoring data using a 2-compartmental model. Linear regression models were used to explore the covariates. RESULTS: The median (IQR) central volume of distribution (Vdc) and clearance (CL) for sufentanil were 4.7 (4.1-5.4) L/kg and 0.651 (0.433-0.751) L/h/kg, respectively. Linear regression models showed relationship between Vdc (L) and GA (r2 = 0.3436; p = 0.0452) as well as BW (r2 = 0.4019; p = 0.0268). Median optimal sufentanil LD and MD were 2.13 (95% CI: 1.78-2.48) μg/kg and 0.29 (95% CI: 0.22-0.37) μg/kg/h, respectively. Median daily COMFORT-B (IQR) scores ranged from 6 to 23 while no significant relationship between pharmacokinetic parameters and COMFORT-B scores was found. DISCUSSION/CONCLUSION: Body weight and gestational age were found as weak covariates for sufentanil distribution, and the dosage regimen was developed for a prospective trial.
Keywords: umělé dýchání; novorozenec; Infant, Newborn; Drug Monitoring; Neonate; Humans; Dosage regimen; monitorování léčiv; sufentanil; gestační stáří; Dose-Response Relationship, Drug; Female; Models, Biological; tkáňová distribuce; Critical care; lidé; Analgesics, Opioid; ženské pohlaví; Tissue Distribution; Male; Retrospective Studies; opioidní analgetika; biologické modely; vztah mezi dávkou a účinkem léčiva; retrospektivní studie; Body Weight; Sufentanil; Pharmacokinetics; tělesná hmotnost; mužské pohlaví; Respiration, Artificial; Gestational Age